Profile of drug resistance mutations among HIV-1-infected Tunisian subjects failing antiretroviral therapy - Jlizi, A; Ben Ammar El Gaaied, A; Slim, A; Tebourski, F; Ben Mamou, M; Ben Chaabane, T; Letaief-Omezzine, A; Chakroun, M; Garbouj, M; Ben Rejeb, S (Archives of virology, 2008)
Three years after the introduction of antiretroviral therapy (ART) in Tunisia (North Africa), we aimed to determine the prevalence of drug resistance mutations in Tunisian HIV-1-infected patients failing ART. Plasma samples of 80 patients were tested for genotypic resistance using two distinct line probe assays, LiPA HIV-1 reverse transcriptase RT and LiPA HIV-1 protease assay. Of the 80 patients, 82.5% showed resistance to at least one antiretroviral molecule. In the RT gene, resistance to nucleoside RT inhibitors (NRTIs) and non-nucleoside RT inhibitors (NNRTIs) were recognized in 66.25 and 37.5%, respectively, with M184V, T215Y and K103N being the codons most frequently involved. Resistance to protease inhibitors (PIs) was found in 46.25% of cases. Despite the presence of different mutations, the viral variants were still susceptible to other RTIs and PIs that are currently not available in Tunisia. Thus, alternative therapeutic options exist but are not yet accessible.